Genesis and development of UCR Index at the University of Costa Rica - Córdoba González, Saray (2016)
This paper describes how UCR index has worked and it evidences an increase in visibility and prestige of the journals of the University of Costa Rica, as well as a greater compliance with the indicators through the years. The indicators used for UCR index are described and the compliance of the indicators between 2011 and 2015 is compared. UCR Index was designed to measure the quality of the journals and, in turn, to improve the allocation of funds and bonuses in an objective and equitable manner in the University. Five quality indicators were defined according to the bibliographic review of other index and national evaluation systems experiences in several countries. The indicators are evaluated annually. After 4 years of application, there is an improvement in the number of index in which the journals participate, an increase of the periodicity, a better Latindex rating of each journal, among others. It is concluded that the UCR index has been effective for the purposes in which it was created.